Human aldehyde dehydrogenase 3A1 (ALDH3A1) exhibits chaperone-like function. (August 2017) - Voulgaridou, Georgia-Persephoni; Tsochantaridis, Ilias; Mantso, Theodora; Franco, Rodrigo; Panayiotidis, Mihalis I.; Pappa, Aglaia
Abstract: Aldehyde dehydrogenase 3A1 (ALDH3A1) is a metabolic enzyme that catalyzes the oxidation of various aldehydes. Certain types of epithelial tissues in mammals, especially those continually exposed to environmental stress (e.g., corneal epithelium), express ALDH3A1 at high levels and its abundance in such tissues is perceived to help to maintain cellular homeostasis under conditions of oxidative stress. Metabolic as well as non-metabolic roles for ALDH3A1 have been associated with its mediated resistance to cellular oxidative stress. In this study, we provide evidence that ALDH3A1 exhibits molecular chaperone-like activity further supporting its multifunctional role. Specifically, we expressed and purified the human ALDH3A1 in E. coli and used the recombinant protein to investigate its in vitro ability to protect Sma I and citrate synthase (from precipitation and/or deactivation) under thermal stress conditions. Our results indicate that recombinant ALDH3A1 exhibits significant chaperone function in vitro . Furthermore, over-expression of the fused histidine-tagged ALDH3A1 confers host E. coli cells with enhanced resistance to thermal shock, while ALDH3A1 over-expression in the human corneal cell line HCE-2 was sufficient for protecting them from the cytotoxic effects of both hydrogen peroxide and tert -butyl hydroperoxide. These results further support the chaperone-like function of human ALDH3A1. Taken together, ALDH3A1, in addition to its primary metabolic role in fundamental cellular detoxification processes, appears to play an essential role in protecting cellular proteins against aggregation under stress conditions.